Simultaneous determination of ascorbic acid, dopamine and uric acid at a nitrogen-doped carbon nanofiber modified electrode. Issue 16 (21st January 2015) - Sun, Jinying; Li, Libo; Zhang, Xueping; Liu, Dong; Lv, Simin; Zhu, Derong; Wu, Tie; You, Tianyan
Abstract : This paper demonstrates high electrocatalytic activity of NCNF/GCE towards small biomolecules. The proposed electrochemical sensor exhibits good selectivity, high sensitivity and excellent stability towards AA, DA and UA simultaneous detection. Abstract : The present work describes a nitrogen-doped carbon nanofiber modified glassy carbon electrode (NCNF/GCE) for simultaneous detection of ascorbic acid (AA), dopamine (DA) and uric acid (UA). NCNF was prepared by combining electrospinning with a thermal treatment method, in which surface etching and nitrogen doping of CNF were achieved by re-utilizing the tail gas produced in the thermal treatment procedure. Attributed to the large surface area and N-doped active sites, NCNF exhibited good electrocatalytic performance towards AA, DA and UA. The oxidation potentials were negatively shifted and the current responses were enhanced greatly compared with bare GCE. Large peak to peak potential separations of 277 mV for AA–DA and 124 mV for DA–UA were obtained at NCNF/GCE by differential pulse voltammetry (DPV). Under the optimized conditions, the as-prepared NCNF/GCE exhibited a wider linear range for AA, DA and UA with low detection limits. The proposed method showed high sensitivity, good selectivity and excellent reproducibility and it was successfully applied for real sample analysis.